Effect of glutathione S-transferase gene polymorphisms on semen quality in patients with idiopathic male infertility. Issue 12 (December 2021) - Zhang, Hongyan; He, Jun; Zhao, Yili; Wu, Qifei; Zou, Tiejun; Sun, Jianhua; Zhu, Haitao; Wang, Xinyang; Sun, Fa; Xing, Junping; Tang, Kaifa
Objective: To investigate the relationship between glutathione S-transferase enzyme ( GSTM1, T1, and P1 ) genetic variants and semen quality in men with idiopathic infertility. Methods: Sperm characteristics were measured using computer-assisted sperm analysis. The malondialdehyde (MDA), nitric oxide (NO), and total antioxidant capacity (TAC) activities were detected by spectroscopic analysis, and 8-hydroxy-2′-deoxyguanosine (8-OHdG) was detected by enzyme-linked immunosorbent assay. Results: This study included 246 idiopathic infertile men and 117 controls. The GSTM1 (−), T1 (−), and M1/T1 (−/−) genotype frequencies significantly differed between the groups. The GSTM1 (−) and T1 (−) genotypes in idiopathic infertile men negatively correlated with sperm concentration, motility, mitochondrial membrane potential, and other parameters. However, these genotypes positively correlated with the amplitude of the lateral head displacement and NO and 8-OHdG levels. The GSTT1 (−) genotype positively correlated with mean angular displacement and MDA activity. GSTM1 (−) and T1 (−) had a synergistic effect on semen quality. Sperm motility, normal morphology, straightness, and TAC were lower and amplitude of lateral head displacement and MDA were higher in the GSTP1(A/G + G/G) group than in the GSTP1(A/A) group among men with idiopathic infertility. Conclusions: GSTM1, T1, and P1 genetic variants may be risk factors for infertility by affecting the semen quality men with idiopathic oligoasthenospermia.